Synthesis, characterization, anti-proliferative, and apoptotic activity of a novel quinazoline-containing 1,2,3-triazole toward three human cancer cells - Mohammad Javad Dehghan-Nayeri; Fariba Peytam; Alireza Foroumadi; Majid Mahdavi (Scientific Reports)
Abstract A novel quinazoline-containing 1,2,3-triazole (4-TCPA) was synthesized to target VEGFR2 signaling for cancer treatment. Although current VEGFR2 inhibitors exhibit strong anticancer activity, their clinical use is limited due to severe side effects. Structural analysis of effective VEGFR2 inhibitors guided the design of 4-TCPA, ensuring the retention of Erlotinib’s essential pharmacophoric features for optimal receptor binding. The compound was tested for its anticancer efficacy against A549 (lung cancer), MCF7 (breast cancer), K562 (leukemia), and human normal fibroblast HFF2 cells. 4-TCPA demonstrated inhibitory activity in nearly all assays, with IC50 concentrations of 35.70 μM for A549, 19.50 μM for MCF7, 5.95 μM for K562, and 135.2 μM for HFF2. Further in vitro biological evaluations examined its mechanistic impact on EGFR, mTOR, Akt, MAPK, and PIK3CA. Apoptotic activity was assessed through Annexin V/PI double staining and caspase-3/7 activation, confirming its ability to induce both early and late apoptosis. Additionally, real-time quantitative PCR (qRT-PCR) was conducted to evaluate the expression levels of Akt, mTOR, MAPK, PIK3CA, EGFR, and VEGFR2. Results showed that 4-TCPA down-regulates these targets in a time-dependent manner, triggering apoptosis across all tested cancer cell lines. The study suggests that 4-TCPA may serve as a promising anticancer agent due to its targeted VEGFR2 inhibition and apoptotic induction, warranting further investigation. These findings support the potential of 4-TCPA as an effective treatment strategy for various cancers.